Activation of Toll-like receptor 7 signaling in labial salivary glands of primary Sjögren's syndrome patients. (28th November 2018) - Shimizu, T; Nakamura, H; Takatani, A; Umeda, M; Horai, Y; Kurushima, S; Michitsuji, T; Nakashima, Y; Kawakami, A
Summary: The aim of this study was to determine the expressions of Toll-like receptors (TLRs) 7–9 and type I interferon (IFN) signal in labial salivary glands (LSGs) and cultured salivary gland epithelial cells (SGECs) from primary Sjögren's syndrome (pSS) patients. We performed an immunohistochemistry analysis of LSGs from 11 patients with pSS as defined by American–European Consensus Group classification criteria and five healthy subjects. The pSS patients' SGECs were analyzed by immunofluorescence and western blotting. IFN-α expression was examined by immunosorbent assay and flow cytometry. Mononuclear cells (MNCs) from pSS patients' LSGs showed TLR-7-dominant expression. B cells, plasma cells and plasmacytoid dendritic cells (pDCs) co-expressed with TLR-7. Myeloid differentiation primary response gene 88 (MyD88), tumor necrosis factor receptor-associated factor 6 (TRAF6) and interferon regulatory factor 7 (IRF7) co-expressed with the pDC marker CD303 in LSGs. Ducts from pSS patients dominantly expressed TLR-7, and TLR-7 in the ducts co-expressed with MyD88, TRAF6 and IRF7. Type I IFNs including IFN-α and IFN-β were detected in MNCs and ducts in pSS patients' LSGs. Increased TRAF6 expression and the nuclear translocation of IRF7 in SGECs were detected by immunofluorescence following loxoribine (a TLR-7 ligand) stimulation despite IFN-β pretreatment. Western blotting showed increased TRAF6 expression in SGECs following IFN-β and loxoribine stimulation. Although no increase in IFN-α was detected in supernatant from stimulated SGECs, the IFN-α in supernatant from stimulated peripheral blood pDCs from pSS patients was significantly increased. Our findings suggest that TLR-7 is dominantly expressed in both MNCs and ducts with downstream signals for type I IFNs, indicating that TLR7-dominant innate immunity is related to the development of sialadenitis in pSS. Graphical Abstract: